Farm animal genetic resources: technical considerations for policy-makers concerning conservation and use: Policy Brief - March 2006 - CGIAR Systemwide Genetic Resources Programme (2006)
This brief was developed by the International Livestock Research Institute (ILRI) and the International Plant Genetic Resources Institute (IPGRI). Special thanks are extended to colleagues at the FAO Commission on Genetic Resources for Food and Agriculture and FAO's Animal Production and Health Division for their contributions.